Mitigating defects in directed energy deposited aluminium 5356 alloy through in-situ workpiece vibration - Mirza Imširović; Uroš Trdan; Damjan Klobčar; Drago Bračun; Aleš Nagode; Laurent Berthe (Journal of Materials Research and Technology)
This study introduces an innovative approach of incorporating in-situ vibrations into Directed Energy Deposition (DED) process, utilizing aluminium 5356 wire, a welding arc heat source, and an electromagnetic vibration system. The findings underscore the method's efficacy in mitigating defects of aluminium 5356 alloy fabricated part. Specifically, the anisotropic distribution of residual stress was reduced by 60%, leading to improved structural integrity. Moreover, the application of in-situ vibrations resulted in a marked reduction in surface waviness, thereby enhancing surface quality and increasing the building efficiency factor by 14% (from 78.5% to 92.25%). Gas porosity was substantially decreased, with a reduction from 1.5 ± 0.04% in as-built parts (AB) to 0.34 ± 0.07% in vibration-assisted (VA) parts. A notable 25% reduction in grain size was observed. The synergistic effect of vibrations and lower interpass temperatures effectively influenced the solidification kinetics, reducing microstructural anisotropy by eliminating characteristic columnar growth and promoting the formation of equiaxed grains. Tensile tests confirmed elimination of anisotropy in strength, with the ultimate tensile strength deviation between the x and z directions of less than 0.4% for VA samples, compared to 7.9% for AB samples. Analysis of secondary phases confirmed a homogenisation effect, evidenced by a lower segregation rate and more finely dispersed peaks of magnesium and iron-enriched precipitates in the VA samples compared to the AB ones (3.57 ± 3.42 μm2 vs. 11.28 ± 12.49 μm2). These results highlight the substantial potential of vibration-assisted DED in improving the properties of manufactured parts.